Occurrence of third-generation cephalosporin-resistant Escherichia coli in European hedgehogs (Erinaceus europaeus) from a wildlife rescue centre in Lombardy, Northern Italy - S. Raineri; A. Gazzola; G. Dilio; S. Ventura; A. M. Maisano; F. Guarneri; N. Formenti; G. L. Alborali; C. F. Magistrali; J. Filipe; Maria Cristina Rapi; G. Grilli (Veterinary Research Communications, 2026)
Hedgehogs represent a promising indicator for evaluating environmental health. We investigated the occurrence of third-generation cephalosporin-resistant (3GCR) Escherichia coli in intestinal contents from 49 European hedgehogs ( Erinaceus europaeus ) deceased at a Wildlife Rescue Centre in Lombardy, Northern Italy. Bacteriological analysis was performed to isolate 3GCR- E. coli ; antimicrobial-resistance (AMR) profiles of the isolates were evaluated by broth dilution (MIC). The presence of bla CTX−M, bla TEM , bla SHV , bla CMY−2 genes was assessed by PCR assay. 3GCR- E. coli were detected in 51% of the examined hedgehogs ( n = 25/49). The majority of the isolates were multidrug resistant (MDR); resistance was recorded against the β-lactams cefotaxime, cefazolin, and ampicillin in 100% ( n = 25/25) of isolates while amoxicillin/clavulanic acid in 52% ( n = 13/25). Resistance against enrofloxacin and flumequine was found in 92% ( n = 23/25) of isolates and tetracycline in 64% ( n = 16/25). All the isolates were susceptible to colistin and florfenicol, and most of them were susceptible to kanamycin (96%, n = 24/25). The most frequently detected resistance gene was bla TEM (52%, n = 13/25), followed by bla SHV (36%, n = 9/25) and bla CTX−M (28%, n = 7/25). Seven isolates carried two ESBL genes, five being bla TEM / bla SHV , and two bla TEM / bla CTX−M . No isolates harbored bla CMY−2 gene. Our study provides the first data on the occurrance of 3GCR- E. coli in European hedgehogs admitted to a wildlife rescue centre in Northern Italy. However, since the sampled animals were not collected through a field-based survey, the findings should not be considered representative of the wider free-ranging population. Nonetheless, resistance profiles and genomic characterization of these isolates provide useful information on AMR circulation in human-impacted environments.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Chemically untreated recycled silicon from PV panels for the sustainable production of Li-ion battery anodes - M. L. Protopapa; E. Burresi; L. Capodieci; D. Carbone; A. Fiore; S. Grilli; B. Palazzo; M. Palmisano; E. Pesce; E. Salernitano; M. Schioppa; N. Taurisano; et al. (Clean Technologies and Environmental Policy, 2026)

Dynamics of circulating lipoproteins and lipids in Brown Skua (Stercorarius antarcticus lonnbergi) during the breeding cycle - A. E. Ibañez; M. Y. Pasquevich; N. Fernandez Machulsky; G. Berg; H. Heras; D. Montalti; M. Graña Grilli (Polar Biology, 2021)

At‐vessel mortality of skates (Rajidae) taken in coastal fisheries and evidence of longer‐term survival - J. R. Ellis; G. J. Burt; G. Grilli; S. R. McCully Phillips; T. L. Catchpole; D. L. Maxwell (Journal of Fish Biology, 2018)
Data on the vigour and at‐vessel mortality (AVM) of 6798 skates (comprising Raja clavata n = 6295; R. brachyura n = 208; R. undulata n = 185, R. montagui n = 98 and R. microocellata n = 12) captured by commercial fishing vessels in the inshore waters of the southern North Sea and English Channel were recorded. AVM in longline fisheries averaged 0·44% across five vessels (0–1·47%), although skates were usually unhooked manually and did not usually pass through a bait‐stripper. AVM in otter trawls averaged 0·76% (0–2·35%), from four vessels fishing with tow durations of R. clavata caught by longline and tangle nets in better condition than those captured by otter trawl or drift trammel net. Similarly, R. undulata caught by tangle net were in better condition than those caught by otter trawl. The vigour of R. undulata was also found to be higher than other skate species for both trawl and tangle net. In total, 5283 skates were tagged with Petersen discs and released, with recapture rates for the various combinations of vessel and gear ranging up to 24·8% for R. clavata . Whilst confirming a degree of post‐release survival, quantitative estimates of post‐release mortality for skates remain unknown.

Mycorrhizal fungi affect plant growth: experimental evidence comparing native and invasive hosts in the context of forest fragmentation - G. Grilli; C. Urcelay; M. S. Longo; L. Galetto (Plant Ecology, 2014)

Isolation of Pseudobutyrivibrio ruminis and Pseudobutyrivibrio xylanivorans from rumen of Creole goats fed native forage diet - D. J. Grilli; M. E. Cerón; S. Paez; V. Egea; L. Schnittger; S. Cravero; M. Sosa Escudero; L. Allegretti; G. N. Arenas (Folia Microbiologica, 2013)

Genomic instability in blood cells is able to predict the oral cancer risk: an experimental study in rats - Daniel A. Ribeiro; Daniela G. Grilli; Daisy M. F. Salvadori (Journal of Molecular Histology, 2008)

Oxygen supply modulates MCP-1 release in monocytes from young and aged rats: Decrease of MCP-1 transcription and translation is age-related - M. Reale; C. Di Giulio; M. Cacchio; R.C. Barbacane; A. Grilli; G. Bianchi; M. Di Gioacchino; M. Felaco; P. Conti (Molecular and Cellular Biochemistry, 2003)